Antimicrobial activity of the seed and callus biomass extract of Linum Usitatissimum L. Against some strains of clinically important pathogens - VIJAY D. MENDHULKAR,; SWATI PRAKASH SAKHARE, (International Journal of Pharma and Bio Sciences, 2017)
Antimicrobial activity of seed extract and callus biomass extract of Linum usitatissimum L. was studied using ethanol as solvent against some strains of clinically important pathogens that include bacterial strains Bacillus cereus, Klebsiella pneumoniae, and fungal strains Candida albicans and Aspergillus niger. The extraction was done by the Soxhlet method and its inhibitory effect was investigated using agar disc diffusion method. Bacillus cereus showed the highest zone of inhibition 8.3±0.57 mm for seed extract and 13.3±1.15mm for callus biomass extract, against Klebsiella pneumoniae. These results were compared with the reference drug Amikacin which was found extremely resistant at the concentration of 100 mcg/mL for both Bacillus cereus and Klebsiella pneumoniae. In case of the fungal strains, Candida albicans showed the highest zone of inhibition 9.3±0.57mm for seed extract and 14.6±0.57mm for callus biomass extract, against Aspergillus niger. The reference drug Fluconazole was resistant at the concentration of 150 mcg/mL against Candida albicans but non-resistant against Aspergillus niger. However, it is interesting to note that callus ethanolic extracts revealed a higher degree of antimicrobial activity than seed ethanolic extract.